2011
DOI: 10.1038/ja.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetospora iriomotensis sp. nov., a novel actinomycete isolated from a lichen sample

Abstract: An actinomycete strain, IR73-Li102 T , was isolated from a lichen sample obtained from Iriomote Island, Japan, and subsequently characterized using a polyphasic approach. Comparative 16S rRNA gene sequence analysis revealed that strain IR73-Li102 T had the highest sequence similarities with Actinomycetospora chiangmaiensis YIM 0006 T (98.3%), A. corticola 014-5 T (98.1%) and A. rishiriensis RI109-Li102 T (98.0%). However, DNA-DNA hybridization assays, as well as physiological and biochemical analyzes, showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Search of special ecological niches along with new methods of isolation of novel genera/species of actinobacteria may lead to the identification of new gene clusters, and hence, new products (Xu et al, 2010 ). Researchers are now focusing on the isolation of actinobacteria from diverse habitats like oceans (Subramani and Aalbersberg, 2013 ), extreme environments (Tang et al, 2003 ; Hamedi et al, 2013 ), inner tissues of plants (Chankhamhaengdecha et al, 2013 ), animals excreta (Cao et al, 2012 ), algae, and lichens (González et al, 2005 ; Yamamura et al, 2011 ). Hence, it is highly encouraging to explore the actinobacteria inhabiting special niches like extremophilic plants for discovering hitherto unexploited strains.…”
Section: Introductionmentioning
confidence: 99%
“…Search of special ecological niches along with new methods of isolation of novel genera/species of actinobacteria may lead to the identification of new gene clusters, and hence, new products (Xu et al, 2010 ). Researchers are now focusing on the isolation of actinobacteria from diverse habitats like oceans (Subramani and Aalbersberg, 2013 ), extreme environments (Tang et al, 2003 ; Hamedi et al, 2013 ), inner tissues of plants (Chankhamhaengdecha et al, 2013 ), animals excreta (Cao et al, 2012 ), algae, and lichens (González et al, 2005 ; Yamamura et al, 2011 ). Hence, it is highly encouraging to explore the actinobacteria inhabiting special niches like extremophilic plants for discovering hitherto unexploited strains.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have described the isolation of different species of actinomycete from lichen, such as Actinomycetospora iriomotensis (Yamamura et al, 2011a), Actinomycetospora rishiriensis (Yamamura et al, 2011b) and Nocardioides exalbidus (Li et al, 2007). In the course of our investigation into the diversity of actinomycetes in Thailand, we obtained strain LDG1-22 T from lichen Flavoparmelia sp.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] During the screening of lichen-associated actinobacteria, we isolated a novel actinobacterium (strain RI148-Li105 T ) from a foliaceous lichen sample collected from Rishiri Island, Hokkaido, Japan. Comparative 16S rRNA gene sequence analysis revealed that the isolate is related to the genus Luteimicrobium.…”
Section: Introductionmentioning
confidence: 99%